Sikap Mahasiswa Universitas PGRI Palangka Raya Terhadap Pelestarian Lingkungan - Dedy Norsandi (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2014)
The objective of the research is to study the relationship between knowledge about ecosystem, perception about environmental health and motivation toward the environmental preservation and students attitudes toward the environmental conservation. The total number of sample were 120 students chosen by multistage random sampling at the University PGRI Palangka Raya. The research indicates that there are positive correlation between: (1) knowledge about ecosystem and students' attitudes toward the environmental conservation, (2) perception about environmental health and students' attitudes toward the environmental conservation and (3) motivation toward environmental preservation and students' attitudes toward the environmental conservation. Therefore, the higher the levels of knowledge about ecosystem, perception about environmental health and motivation toward environmental preservation, the more positive students' attitudes toward the environmental conservation will be.